UPAYA PENINGATAN KEAKTIFAN BELAJAR MAHASISWA PADA PERKULIAHAN MOTOR BAKAR MAHASISWA PRODI PTM FKIM UNS MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Agal Dani Argo; Ranto Ranto; Towip Towip (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
This research aims to determine the application of the Problem Based Learning (PBL) learning model in an effort to improve student learning activity in the 2022 2th Semester  Student Internal Combustion Motor course, Mechanical Engineering Education Study Program, Faculty of Teacher Training and Education, Sebelas Maret University, Surakarta.This research is a classroom action research (CAR) model by Kemmis and Mc. Taggart with 3 cycles that focuses on action in an effort to increase student learning activities in the Fuel Motor course. Data collection techniques using the observation method. Furthermore, the research subjects were students of the Class A Combustion Motorcycle Lecture Semester 2 of the 2023 Mechanical Engineering Education Study Program with a total of 42 Class A Combustion Motorcycle Lecture students. The analysis used in this research is a qualitative descriptive analysis technique. Based on the research results, by implementing the Problem Based Learning (PBL) learning model, student learning activity improved. And to find out the results of improving student learning activities, students Based on research, it shows that student activity and learning outcomes in the Fuel Motor course in class A PTM FKIP UNS are relatively low. Based on data obtained at the pre-cycle stage, the percentage of all indicators was 38.44%, cycle 1 the percentage of all indicators was 68.06% and cycle 2 the percentage of all indicators was 78.04%. And cycle 3 the percentage of all indicators is 82.06%.This research produces the following conclusions. The results of the analysis and discussion of the research based on research observation, the following conclusions can be drawn: The application of the Problem Based Learning (PBL) learning model can improve student learning activity in the PTM FKIP UNS Internal Combustion Motor course 2th Semester 2023